AN ANALYSIS OF POLITENESS STRATEGIES ON CHARACTER TORI VEGA IN NICKELODEON COMEDY SERIES “VICTORIOUS” - Adelia Abubakar; Rahman Taufiqriyanto Dako; Jefriyanto Saud (Indonesian Journal of Education (INJOE), 2025)
This study aims to analyze the types of politeness strategies and contextual factors influencing their selection by the character Tori Vega in the Nickelodeon comedy series, Victorious. Communication is fundemental for social beings, and politeness is crucial for maintaining harmonious social interactions. While many studies focus on politeness strategies, few examine them in the context of American comedy series. Using a qualitative research approach and interpretative content analysis, this study collects data from the dialogue of Tori Vega across the first 10 episodes of Victorious season 1. The theoritical framework is based on Brown and Levinson’s (1987) politeness theory, which includes Positive Politeness, Negative Politeness, Bald On-Record, and Off-Record Strategies. The findings indicate that Tori Vega employs all four strategies in her interactions. For instance, She uses Positive Politeness for compliments (e.g., “Oh my God, You’re fantastic!”), Bald On-Record for direct assertion, and Off-Record for indirect communication and sarcasm to save face or create humor. Contextual factors like social distance, self-esteem maintenance, and the need for clarity influence her strategy selection. The research contributes to pragmatics by exploring politeness in pop culture media.